Elusive Europeanisation: Liberalising road haulage in the European Union - Dieter Kerwer; Michael Teutsch (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
Having established itself as a robust level of governance, the European Union now potentially affects its member states in more ways than ever before. Road haulage policy is an area in which a strong impact of European Union policy-making can be expected. Liberalisation at the European level contradicts widespread interventionist transport policy traditions of the member states. In this article we ask how France, Germany, and Italy, three countries with an interventionist transport policy tradition, are affected by European liberalisation. We find that all of the three countries have abandoned their policy traditions. However, domestic factors were more important than European factors in bringing about this change. European influence did not severely curtail national policy-making autonomy. In transport policy, Europeanisation is elusive because national institutional intermediation largely muffled the impact of European policy-making.
Keywords: 330; EU-Politik; Straßengüterverkehr; Deregulierung; Institutioneller Wandel; Frankreich; Deutschland; Italien; EU-Verkehrspolitik